Tithonian-Valanginian calcareous dinoflagellate cysts from West Balkan Mountains, Bulgaria and Southern Mendoza Neuquén Basin, Argentina: Vertical distribution and long distance correlations - Ivanova, Daria K. (2017)
Calcareous cysts of dinoflagellates (Calciodinelloideae=Calcisphaerulidae) constitute one of the most common calcareous microfossil groups widely distributed in the pelagic sediments in the Tethyan realm during Late Jurassic Early Cretaceous time, and have significant stratigraphic importance (Ivanova and Kietzmann [1]).The marine sediments of the West Balkan Mountains (Bulgaria) and Andean region (Argentina) have an excellent record of calcareous microfossils. The present study embraces the biostratigraphic investigations on calcareous dinoflagellate cyst from succession of pelagic limestones of Tithonian Valanginian age in two sections in the West Balkan Mts. and three sections in the Southern Mendoza Neuquén Basin. Detailed micropaleontological studies of complete pelagic sections excellently exposed in the both regions are conducted with the aim of establishing a major event in vertical distribution of the calcareous cysts of dinoflagellatesThe following dinocysts zones previously proposed for the Tethyan realm (Ivanova in: Lakova et al. [2]) are confirmed in the southern Mendoza Neuquen Basin: Carpistomiosphaera tithonica Zone (spans the Kimmeridgian-Tithonian boundary interval); Parastomiosphaera malmica Zone (corresponds to Early Tithonian); Colomisphaera tenuis Zone (the FO of Colomisphaera tenuis corresponds exactly to the base of Dobeni Subzone of the Chitiniodella Zone in latest Early Tithonian, former the base of the Middle Tithonian); Colomisphaera fortis/Stomiosphaerina proxima Zone (the C. fortis/S. proxima Zones in the Tethyan realm are two separate zones, which cannot be separated in the Andean region); Stomiosphaera wanneri Zone (range of the zone as latest Late Berriasian, except its very top); Colomisphaera conferta Zone (uppermost Berriasian ? Early Valanginian boundary interval) and Carpistomiosphaera valanginiana zone (the zone was first defined by Ivanova in: Lakova et al., 1999 as new and comparable to the calpionellid Tintinnopsella Zone, Late Valanginian. New research, however, witness the FO of the index-species probably in the Early Valanginian). The range of the zones is based on Geological time scale (Gradstein et al. [3]).The Late Jurassic ? Early Cretaceous marine sediments of the West Balkan Mts. (Bulgaria) and the Andean region (Argentina) show an excellent record of calcareous dinoflagellate cysts. The calcareous dinocysts associations allow dating Late Jurassic-Early Cretaceous lithostratigraphic units within marine sediments of the West Balkan Mts. (Bulgaria) and the Southern Mendoza Neuquén Basin (Argentina), they provide valuable information when specifying the biostratigraphy and paleoenvironment. Quantitative analyses are performed to the representatives of calcareous dinocysts in order to evaluate the species diversity through time, relative abundance along the sections studied and a possible relationship between calcareous dinocysts distribution and eustatic changes of the sea level. Calcareous dinocysts have provided a tremendous amount of data that have advanced our understanding of Tethyan realm history and the results obtained permit excellent vertical distribution and long distance correlations in both the West Balkan Mts. and the Andean region.